Use of the System S2o3 (2-) -O2 for the Leaching of Precious Metals Contained in a Mineral From Molango in the State of Hidalgo, Mexico - RoldÃ¡n-Contreras, Edmundo; HernÃ¡ndez-Ãvila, Juan; Cerecedo-SÃ¡enz, Eduardo; Reyes-Valderrama, Ma. Isabel; Salinas-RodrÃguez, Eleazar (European Scientific Journal, ESJ, 2018)
The newer tendencies of research, related with the leaching of precious metals, involves the use of non toxic reagents that allows the leaching of a mineral of sedimentary origin using the system S2 - O3 2- - O2. Prior to thisprocess, the mineral was characterized by Scanning Electron Microscopy (SEM) in conjunction with Energy Dispersive Spectrometry of X â€“ rays (EDS), X- ray mapping. Finally, the chemical composition was executed by Inductively Coupled Plasma Spectrometry (ICP). According to the results obtained, it was possible to determine that the mineral studied has adequate contents of gold, palladium, silver, and platinum. And after the leaching process, it could be possible to leach the gold and palladium that it contains, getting recoveries of 90% and 85 %, respectively. In the case of silver, a redissolution or precipitation could occur during the first minutes of reaction.